Cost-effectiveness of weekly gastro-resistant risedronate 35 mg, compared with weekly alendronate 70 mg tablets, in the treatment of postmenopausal osteoporosis in Spain - Enrique Casado; Jose Rosas; Carlos Rubio-Terres; Dario Rubio-Rodriguez; Mitra Boolell; Ignacio Aristegui (Becaris Publishing Limited, 2023)
Aim: To estimate the cost-effectiveness of treating postmenopausal osteoporosis (PMO) with weekly gastro-resistant risedronate 35 mg gastro-resistant tablets (RIS-GR), compared with weekly alendronate 70 mg tablets (ALN) in Spain. Methods: A probabilistic analysis (second-orderMonte Carlo simulation) was performed with a time horizon of 5 years, from the perspective of the Spanish National Health System. The bone fracture probabilities were obtained from a cohort study of 3614 women from USA withPMOtreated with RIS-GR (1807) or ALN (1807) (Thomasius, 2022). The pharmacological cost and the cost of fractures were obtained from Spanish sources (€ 2022). The utilities of patients with and without fracture (qualityadjusted life years [QALYs]) were obtained from the medical literature. Results: Compared with ALN, treatment with RIS-GR can avoid 79 fractures (between 75 and 82) every 1000 patients treated, and 0.0119 QALYs would be gained (between 0.0098 and 0.0140) per patient. Additionally, GR-RIS would generate a cost saving per patient of €1994 (€1437-2904) with a probability of 99.7%. The scenario analyses confirmed the stability of the base case results. Conclusion: According to this study, RIS-GR would be the dominant treatment (lower costs with QALY gain) compared with ALN.